Laboratory diagnosis of congenital syphilis by immunoglobulin M (IgM) and IgA immunoblotting. - Schmitz, J L (1994)
We screened cord blood or serum samples from 101 infants at risk for congenital syphilis and serum samples from their mothers for immunoglobulin G (IgG), IgM, and IgA antibodies to Treponema pallidum by western blotting (immunoblotting). Clinical evaluation showed that six infants had signs and/or symptoms consistent with congenital syphilis. The sera from five of these infants were IgM blot positive, and four were IgA blot positive. Four asymptomatic infants had serologic evidence of congenital syphilis. The sera from three of these infants were IgM blot positive, and two were IgA blot positive. However, the IgM reactivity of the serum from one asymptomatic infant, which was also IgA positive, was abolished by protein G treatment. An IgM capture enzyme-linked immunosorbent assay corroborated the presence of IgM antibodies in six of seven IgM blot-reactive sera. Overall, for detection of symptomatic congenital syphilis, a sensitivity of 83% for IgM blotting and 67% for IgA blotting was obtained. The significance of positive IgM or IgA Western blots for asymptomatic infants requires further study to confirm infection in these infants.